PREVENTIVE EFFECT OF INTRACISTERNAL HEPARIN FOR PROLIFERATIVE ANGIOPATHY AFTER EXPERIMENTAL SUBARACHNOID HEMORRHAGE IN RATS - (:unkn) unknown (SPRINGER-VERLAG WIEN, 1994)
Proliferative angiopathy represents the morphological basis of delayed cerebral vasospasm. The initial vasoconstriction and endothelial damage of the vasospastic arteries leads to an exaggerated response of the smooth muscle cells within the media leading to subintimal thickening and myonecrosis. Heparin reduces the exposure of the media to platelet derived growth factor, a mitogen from aggregating platelets responsible for the migration and proliferation of the myofibroblasts. Since systemic heparin in the setting of a subarachnoid haemorrhage would be unacceptable, we have tested the effect of heparin on proliferative angiopathy by injecting autologous non-heparinized blood into two groups of rats (N = 12 each) and then inject the heparin into the spinal fluid of one group after one hour. We were able to show histologically that intracisternal heparin injection after the subarachnoid haemorrhage has reduced the vascular wall changes to a great degree. Heparinization of the cerebrospinal fluid carried out in conjunction with early operation for aneurysms may be a promising approach to prevent the morbid complications of SAH in the clinical setting.
Keywords: EXPERIMENTAL SUBARACHNOID HEMORRHAGE; HEPARIN; RAT; TRANSMISSION ELECTRON MICROSCOPY; MUSCLE CELL-PROLIFERATION; ARTERIAL-WALL CHANGES; CEREBRAL VASOSPASM; ANIMAL-MODEL; HEMORRHAGE; INHIBITION; INJURY; MANAGEMENT; MICROSCOPY; KINETICS